1,2-diacylglycerol content in thoracic aorta of spontaneously hypertensive rats - Okumura, Kenji; Kondo, Junichiro; Shirai, Yoshihisa; Muramatsu, Masahito; Yamada, Yumiko; Hashimoto, Hidekazu; Ito, Takayuki (Hypertension, 1990)
Phosphoinositide metabolism participates in the control of cell calcium homeostasis. Because a notable neutral lipid (1,2-diacylglycerol) is generated from phosphoinositide hydrolysis and is assumed to be a secondary messenger, we determined 1,2-diacylglycerol content and its fatty acid profiles in the thoracic aorta of spontaneously hypertensive rats (SHR) and compared it with those of nonnotenslve Wistar-Kyoto (WKY) rats. After the aorta was exposed to 10 M norepinephrine as a stimulant, 1,2-diacylglycerol content in SHR was significantly higher by 33% than in WKY rats at 4 weeks of age, whereas there was no difference in 1,2-diacylglycerol content between the two strains at 20 weeks of age. Before norepinephrine stimulation, there was no significant difference in 1,2-diacylglycerol level between the two strains at 4 weeks of age. Analysis on a gas chromatograph showed that 1,2-diacylglycerol was composed of similar molecular species of fatty acids in aortas obtained from SHR and WKY rats. On the other hand, the cholesterol content of aortas was higher in SHR than in WKY rats at 20 weeks of age, whereas the difference at 4 weeks was not significant Phosphatidylcholine, phosphatidylethanolamine, and triglyceride showed no significant difference between the two strains. It is concluded that norepinephrine-induced 1,2-diacylglycerol production increases in the thoracic aorta of SHR before the development of hypertension.